Ancient lowland Maya complexity as revealed by airborne laser scanning of northern Guatemala - Canuto, Marcello A.; Estrada-Belli, Francisco; Garrison, Thomas G.; Houston, Stephen D.; Acuña, Mary Jane; Kováč, Milan; Marken, Damien; Nondédéo, Philippe; Auld-Thomas, Luke; Castanet, Cyril; Chatelain, David; Chiriboga, Carlos R.; et al. (Science (American Association for the Advancement of Science), 2018)
Lidar (a type of airborne laser scanning) provides a powerful technique for three-dimensional mapping of topographic features. It is proving to be a valuable tool in archaeology, particularly where the remains of structures may be hidden beneath forest canopies. Canuto et al. present lidar data covering more than 2000 square kilometers of lowland Guatemala, which encompasses ancient settlements of the Classic Maya civilization (see the Perspective by Ford and Horn). The data yielded population estimates, measures of agricultural intensification, and evidence of investment in landscape-transforming infrastructure. The findings indicate that this Lowland Maya society was a regionally interconnected network of densely populated and defended cities, which were sustained by an array of agricultural practices that optimized land productivity and the interactions between rural and urban communities. Science , this issue p. eaau0137 ; see also p. 1313 Lidar data elucidate the demography, agriculture, and political economy of Classic Lowland Maya civilization. Lowland Maya civilization flourished in the tropical region of the Yucatan peninsula and environs for more than 2500 years (~1000 BCE to 1500 CE). Known for its sophistication in writing, art, architecture, astronomy, and mathematics, Maya civilization still poses questions about the nature of its cities and surrounding populations because of its location in an inaccessible forest. In 2016, an aerial lidar survey across 2144 square kilometers of northern Guatemala mapped natural terrain and archaeological features over several distinct areas. We present results from these data, revealing interconnected urban settlement and landscapes with extensive infrastructural development. Studied through a joint international effort of interdisciplinary teams sharing protocols, this lidar survey compels a reevaluation of Maya demography, agriculture, and political economy and suggests future avenues of field research.